(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the difficulties and solutions involved in translating specialized social domain terms from French into Uzbek. The study highlights issues of terminological equivalence, cultural and institutional differences, as well as semantic and pragmatic features of social terms. Based on a comparative and contextual analysis, the article proposes translation strategies such as borrowing, descriptive paraphrase, and functional adaptation. The findings demonstrate that translating social terminology requires an analytical approach grounded in an understanding of the social systems of both languages.